Design, synthesis and molecular modeling study of substituted indoline-2-ones and spiro[indole-heterocycles] with potential activity against Gram-positive bacteria - Radwan Awwad Abdoh; Aanazi Fares Kaed; Al-Agamy Mohammed; Mahrous Gamal Mohammad (Acta Pharmaceutica)
Longstanding and firsthand infectious diseases are challenging community health threats. A new series of isatin derivatives bearing β-hydroxy ketone, chalcone, or spiro-heterocycle moiety, was synthesized in a good yield. Chemical structures of the synthesized compounds were elucidated using spectroscopic techniques and elemental analysis. Antibacterial activities of the compounds were then evaluated in vitro and by in silico modeling. The compounds were more active against Gram-positive bacteria, Staphylococcus aureus (MIC = 0.026–0.226 mmol L−1) and Bacillus subtilis (MIC = 0.348–1.723 mmol L–1) than against Gram-negative bacteria (MIC = 0.817–7.393 mmol L–1). Only 3-hydroxy-3-(2-(2,5-dimethylthiophen-3-yl)-2-oxoethyl)indolin-2-one (1b) was found as active as imipenem against S. aureus (MIC = 0.026 mmol L–1). In silico docking of the compounds in the binding sites of a homology modeled structure of S. aureus histidine kinase-Walk allowed us to shed light on the binding mode of these novel inhibitors. The highest antibacterial activity of 1b is consistent with its highest docking score values against S. aureus histidine kinase.